Standards and power - Lawler, Diego (Mechane, 2025)
Standards are foundational elements that structure the artificial world, influencing the ontological, epistemological, normative, and axiological dimensions of human life. As technical artifacts, they regulate interactions, delineate permissible actions, and subtly distribute power within complex sociotechnical networks. Although often invisible in everyday experience, standards reflect and perpetuate the interests of dominant actors, becoming deeply embedded in global systems and societal values. This article critiques the functionalist perspective on standards and introduces a philosophical framework that positions them as artifacts inseparable from power dynamics. It examines how standards function as instruments of governance and control, with particular attention to their geopolitical implications. The article also highlights the potential for resistance, arguing that the negotiation and contestation of standards can challenge hegemonic norms and foster alternative practices. Ultimately, this work calls for further investigation into the intersection of standards, power, and imperialism to better understand how global hierarchies are reinforced through standardization.